DRUG TOXICITY (AUSHADHA VYAPATA) IN AYURVEDA - Kumar Sahoo, Sushanta; Singh, Shailendra; Kumar Gupta, Ramesh; Lakshmi, Vijay (International Journal of Ayurveda and Pharma Research, 2015)
In Ayurvedic view Aushadha Vyapata means the complications of a drug or any extra actions of the drug / medicine in human body except the intended action. This can be correlated with the adverse drug reactions of the modern pharmacology which includes the side effects, untoward effects, toxic effects and idiosyncratic effects. Many questions are now being raised by the scientific and non-scientific community worldwide regarding the documentation of safety and efficacy of Ayurvedic Medicines. A couple of studies done in USA have raised very serious questions in this regards. Now a day the concept of pharmacovigilance has been started by WHO to monitor ADR (adverse drug reaction), report and record. Ancient Ayurvedic scholars were very much aware about the drug toxicity and keeping it in the mind they have described Aushadha vyapata in their classics elaborately which reflect their concern about untoward effect of Ayurvedic drugs.